The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3390/fib12010006
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Chemical Treatment on the Properties of Colombian Banana and Coir Fibers and Their Adhesion Behavior on Polylactic Acid and Unsaturated Polyester Matrices

Ismael Barrera-Fajardo,
Oswaldo Rivero-Romero,
Jimy Unfried-Silgado

Abstract: In this work, the adhesion behavior of chemically treated banana and coir Colombian fibers embedded in polylactic acid (PLA) and unsaturated polyester resin (UPR) matrices was investigated. Both types of fibers were treated with a 5 wt.% sodium hydroxide solution for one hour. The properties of treated and untreated fibers were determined by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and tensile tests. To evaluate the adhesion behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…This proves that the fiber volume fraction affects the evaluation results of IFSS, and previous experiments have had difficulty controlling the fiber volume fraction. Falkenreck et al [21], Barrera-Fajardo et al [22], and Liu et al [23] reported the effects of a natural fiber surface treatment on the mechanical properties of composites. These mechanical properties include tensile strength, bending strength, and surface friction, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…This proves that the fiber volume fraction affects the evaluation results of IFSS, and previous experiments have had difficulty controlling the fiber volume fraction. Falkenreck et al [21], Barrera-Fajardo et al [22], and Liu et al [23] reported the effects of a natural fiber surface treatment on the mechanical properties of composites. These mechanical properties include tensile strength, bending strength, and surface friction, and so on.…”
Section: Introductionmentioning
confidence: 99%